An analytical model of stresses in adhesive bonded interface between steel and bamboo plywood. (1st January 2015) - Zhang, Zhen-wen; Li, Yu-shun; Liu, Rui
Highlights: An analytical model for unbalanced adhesive bonded joint is proposed. Explicit closed-form expressions for the shear stress and peel stress are derived. The initial debonding is caused by the shear stress and peel stress. The initial debonding is located in a tiny area close to the end of overlap. Increasing the section stiffness of bamboo plywood can reduce the concentration of stresses. Abstract: Bamboo–steel composite structure is a newly developed type of structure. Structural adhesive is used to combine bamboo plywood with cold-formed thin-walled steel. Hence, the mechanical performance of the bonded interface between steel and bamboo plywood is crucial to the Bamboo–steel composite structure. To investigate the mechanical performance of the adhesive bonded interface, an analytical model for unbalanced adhesive bonded joint is proposed, and explicit closed-form expressions for the shear stress and peel stress in the adhesive layer, bamboo plywood, steel sheet and their interfaces are derived. The stresses distribution predicted by this model indicates that the initial debonding is caused by the shear stress and peel stress at the interface between bamboo plywood and adhesive layer, and is located in a tiny area close to the end of overlap. Analysis of the variables influencing the stresses distribution suggests increasing the section stiffness of bamboo plywood has a significant effect on reducing the concentration of stresses.